Convolution operators associated with vector measures - Robdera, Mangatiana A.; Saab, Paulette (Cambridge University Press, 1998)
In this note, we present a thorough investigation of convolution operators that are naturally associated to vector measures. We characterize those convolution operators that are weakly compact and compact on L1(G) and C(G) as well as those that are p-summing, (1 ? p ? ?) and nuclear on C(G).